Chemical degradation of PFSA ionomer binder in PEMFC's catalyst layer. (9th August 2018) - El Kaddouri, Assma; Flandin, Lionel; Bas, Corine
Abstract: The degradation of perfluorinated sulfonic acid ionomer (PFSA) binder in catalyst layer of Proton Exchange Membrane Fuel Cell (PEMFC) was investigated on Membrane-Electrode-Assemblies (MEA) operated up to 10400 h in base load conditions for telecom relay. Soxhlet extractions in water media were performed on the catalyst layer deposited on the Gas Diffusion Layer (GDL). The Soxhlet solutions for anode and cathode sides were analyzed by 19 F NMR spectroscopy showing degradation products originating from the ionomer in the catalyst layer. At the cathode side, 1, 2, 2-tetrafluoro-2-(1, 2, 2, 2-tetrafluoroethoxy)ethanesulfonic acid were clearly identified. This suggests that PFSA binder degradation originated from an H and/or OH radical attack of the side chain. The NMR quantification of the degradation products allows a fruitful comparison with the literature. The degradation mechanism of the PFSA binder is different from that of the membrane. Highlights: Degradation product of the ionomer binder was identified. The degradation of the ionomer in the Catalyst layer is localized on the side chain of PFSA. Same degradation rate occurs on cathode and anode electrodes. Degradation pathway for ionomer binder is proposed.